Mathematical self-concept among prospective teachers - Johannis Takaria; Anderson Leonardo Palinussa (International Journal of Evaluation and Research in Education (IJERE), 2020)
Mathematical self-concept (MS-C) is an important construct that prospective mathematics teachers must have in mathematics learning. The aim of the research was to analyze the increase of MS-C of prospective mathematics teachers. The research was quasi-experimental with the design of one group pretest-posttest. The results showed that for prospective teachers, MS-C increased in the medium category while the MS-C indicators achieved in the medium and low categories. The increase of MS-C is due to the effectiveness of collaborative mind mapping (CMM) learning strategy and the process of strengthening MS-C capacity of prospective teachers. The CMM facilitates prospective teachers to construct creative ideas through structured collective ideas that support the increase of MS-C among prospective teacher.